MEMBANGUN KELUARGA SAKINAH - Asad Asad (Tazkiya: Jurnal Pendidikan Islam, 2018)
This study will discuss about family and purpose of how are we develop a good family in this world based on Islam. In Arabic the family can be interpreted as (ahlun / usrah). According to Musthafa al-Maraghi, the family is father and mother, children of the whole family. Family according to M.Quraish Shihab, namely the smallest people who have leaders and members, have a division of tasks and work, as well as rights and obligations for each member. So the family is the smallest community which includes the existence of a father and mother and the descendants of both who have duties and obligations and their respective. The family should be a harmonious, cool and comfortable relationship, full of compassion, so that the family gets calm and tranquility.  Keywords : Membangun, Keluarga, Sakinah